Proteomic and other mass spectrometry based "omics" biomarker discovery and validation in pediatric venous thromboembolism and arterial ischemic stroke: Current state, unmet needs, and future directions - Goldenberg, Neil A.; Everett, Allen D.; Graham, David; Bernard, Timothy J.; Nowak-Göttl, Ulrike (Proteomics. Clinical applications, 2014)
Venous thromboembolism (VTE) and arterial ischemic stroke (AIS) are increasingly‐recognized health conditions in children, with both acute and chronic sequelae. Risk factors for, and pathogenesis of, VTE are readily related to three principal factors, consisting of venous stasis, endothelial damage, and the hypercoagulable state (i.e. thrombophilia), termed the triad of Virchow. In children, greater than 90% of VTE are provoked by an overt clinical risk factor, the most common of which is a central venous catheter. Risk factors for childhood‐onset (beyond the neonatal period) AIS include sickle cell disease, infection, cerebral arteriopathy, and congenital cardiac disease. In perinatal AIS, risk factors are less well‐defined, and have been hypothesized to include maternal‐fetal conditions. While some acquired and inherited thrombophilias have been associated with increased risk of incident and/or recurrent VTE and AIS, knowledge of other diagnostic and prognostic biomarkers of VTE/AIS in children remains quite limited. To date, very few published studies have employed plasma mass spectrometry‐based “omics” approaches (proteomics, lipidomics or metabolomics). Ongoing and future research efforts involving multicenter prospective study‐derived plasma biobanks in pediatric VTE (such as the Kids‐DOTT trial) and AIS (including VIPS) along with new multi‐omics‐compatible sample processing methods offer fertile opportunities for discovery and validation of both novel risk factors and prognostic markers, with great potential to achieve improved prognostic stratification in these diseases.